Colored object detection using 5 dof robot arm based adaptive neuro-fuzzy method - Mujiarto Mujiarto; Asari Djohar; Mumu Komaro; Mohamad Afendee Mohamed; Darmawan Setia Rahayu; W. S. Mada Sanjaya; Mustafa Mamat; Aceng Sambas; Subiyanto Subiyanto (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, an Adaptive Neuro Fuzzy Inference System (ANFIS) based on Arduino microcontroller is applied to the dynamic model of 5 DoF Robot Arm presented. MATLAB is used to detect colored objects based on image processing. Adaptive Neuro Fuzzy Inference System (ANFIS) method is a method for controlling robotic arm based on color detection of camera object and inverse kinematic model of trained data. Finally, the ANFIS algorithm is implemented in the robot arm to select objects and pick up red objects with good accuracy.